An analysis of ebrary Academic Complete at Adelphi University. Issue 1 (2014) - ,
<x xml:space="preserve">Abstract</x> Purpose – This paper aims to examine the academic and financial value of ebrary Academic Complete package to the Adelphi University Libraries. Design/methodology/approach – ebrary provided statistics and this sample was used to analyze subject usage and overlap with the print collection. Findings – It was found that although there was overlap with the print collection, the usage statistics are high enough to warrant continued subscription. Originality/value – This paper case study of Adelphi's issues regarding subscribing to a backfile of e‐books including subject usage, print overlap, and information management.